2012
DOI: 10.1111/j.1432-2277.2012.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide variability in deceased organ donation registries

Abstract: The variability in deceased organ donation registries worldwide has received little attention. We considered all operating registries, where individual wishes about organ donation were recorded in a computerized database. We included registries which recorded an individual's decision to be a donor (donor registry), and registries which only recorded an individual's objection (non-donor registry). We collected information on 15 characteristics including history, design, use and number of registrants for 27 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 10 publications
0
44
0
1
Order By: Relevance
“…However, the initiative's demonstrable efficacy is enhanced when it can be linked to a preexistent online registry, as our study illustrates. There remains great worldwide variability in deceased organ donation registries (19) and Facebook and Donate Life America may be able to participate in the online construction of such resources in countries where they do not exist or are being developed and can be encouraged by the rollout of the donor initiative, that is, Mexico (20-22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the initiative's demonstrable efficacy is enhanced when it can be linked to a preexistent online registry, as our study illustrates. There remains great worldwide variability in deceased organ donation registries (19) and Facebook and Donate Life America may be able to participate in the online construction of such resources in countries where they do not exist or are being developed and can be encouraged by the rollout of the donor initiative, that is, Mexico (20-22).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Geographic differences in organ donor registration and organ donation rates are large and not fully explained by demographics. 6,15 Interventional studies have demonstrated successful approaches to encouraging organ donor registration and organ donation itself. 16 These practices could improve the supply of pediatric-quality kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2012 study comparing characteristics and proportions registered of various registries worldwide, Nova Scotia had the highest proportion of citizens registered, at 65%, followed by New Brunswick (42%), Ontario (18%), Yukon Territory (16%), Quebec (10%) and British Columbia (8%). 2 In Canada, donor registries are "opt-in" registries that record only "yes" responses. People can register for organ and tissue donation when they renew or apply for a new driver's licence or health card at ServiceOntario.…”
Section: Design and Settingmentioning
confidence: 99%
“…1 Canada has an "opt-in" system, whereby citizens can record their donation wishes through a deceased organ donor registry, which can then be used to inform family members in the event of death. 2,3 Increasing the number of registered donors is a key strategy adopted by Canadian organ procurement organizations to improve organ and tissue donation. 2 An important step to increase the registration rate is to identify subpopulations that have lower donor registration rates and to better understand the reasons for nonregistration.…”
mentioning
confidence: 99%